Predicting adventure seeking of young adults: The role of risk, innovativeness and status consumption. Issue 5 (November 2020) - Keane, Matthew; Eastman, Jacqueline K.; Iyer, Rajesh
Graphical abstract: Highlights: Innovativeness in extreme sports increases adventure seeking. Risk aversion negatively affects attitude towards adventure seeking. Status consumption mediates the risk aversion – adventure seeking relationship. Status consumption mediates innovativeness – adventure seeking relationship. Abstract: Extreme sports continue to grow and attract young adults. Research is needed to better understand what motivates athletes to participate in the adventure seeking of extreme sports beyond the need for thrills. The results of a survey utilizing a sample of young educated adults, those more likely to be able to fund adventure seeking, finds that those who are more innovative in the domain of extreme sports and who are less risk averse are more likely to participate in adventure seeking activities. The motivation to consume for status plays a key mediating role between innovativeness, risk aversion, and adventure seeking which suggests that status consumption is a vital individual difference variable in understanding and reaching the adventure seeking young adult. Furthermore, there is no difference by gender in the model tested. The implications for sport marketing managers and future research are discussed.